Influence of Family Business Generation in Indonesia: First, Second, and Third Generational Ownership and Institutional Ownership As Moderation - Mufidah, Eva; Narsa, I Made; Madyan, Muhammad; Bramayudha, Airlangga; Mawardi, Imam (Migration Letters, 2024)
Family company research is a vastly interesting study since family companies are super complex and dynamic business entities with unique characteristics in ownership patterns, management governance, and leadership succession. This study proves the phenomenon occurring that only 30% of family businesses survive from generation I to generation II, and 12% successfully make the transition from generation II to generation III. This study examines the effect of generational ownership in generations I, II, and III on company performance using ROE and ROA proxies with institutional ownership moderation. It uses the theoretical basis, namely agency theory, in family companies that have the potential to experience conflicts of interest between family shareholders and non-family shareholders. This research is quantitative research and uses a sample of 113 family companies during 2010-2020 years in Indonesia using unbalanced panel data obtained from the Indonesia Stock Exchange through OSIRIS. The analysis technique uses regression analysis and moderation regression analysis. The analysis results show the difference in the influence of generations I, II, and III on family companies in Indonesia. The results show a difference in the generational ownership influence in generations I, II, and III. In generation I, the results of generational ownership (go1) have a positive and significant effect on the company’s performance on ROE and ROA. While generation II shows that generational ownership (go2) has a negative and significant effect on ROE, but it does not affect ROA. For generation III, it shows that generational ownership (go3) has no effect on ROE and has a positive and significant effect on ROA.